Study of Non-Load-Bearing Concrete Blocks from Rubber Wood Ash - Rungsaktaweekul, Thaweesak; Kongpun, Teerin; Puangphet, Patumphon; Suwansaard, Apised (Rajamangala University of Technology Tawan-ok Research Journal, 2024)
Study of non-load-bearing concrete blocks from rubber wood ash. Use rubber wood ash in place of type 1 hydraulic cement in the ratio of 0, 5, 10, 15, and 20 percent in the ratio of 1:6, using water in the ratio of 20 percent of the total weight of the mixture. The results of testing the chemical properties of rubber wood ash revealed that rubber wood ash is not classified as a pozzolanic substance. However, it has a high calcium oxide content, which is a factor that causes pozzolanic reactions, disintegrating binders, and has a positive effect on the mechanical properties of concrete. Testing the physical and mechanical properties of concrete blocks from the test results showed that when using rubber wood ash in place of type 1 hydraulic cement in various ratios, a rubber wood ash ratio of 20 percent had the best effect. It has an average density value of 1307.40 kilograms per cubic meter. Average water absorption was equal to 5.46 percent and the average compressive strength values at the curing period of 7, 14, and 28 days were equal to 35.25, 42.19, and 55.22 kilograms per square centimeter, respectively. The values obtained are by TIS 58-2017, non-load bearing type.